2011
DOI: 10.3324/haematol.2011.053058
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole prophylaxis during front-line chemotherapy of acute myeloid leukemia: a single-center, real-life experience

Abstract: The online version of this article has a Supplementary Appendix. BackgroundPosaconazole is effective as primary antifungal prophylaxis of invasive fungal diseases in patients with acute myeloid leukemia. Design and MethodsThe impact of primary antifungal prophylaxis administered during front-line chemotherapy for acute myeloid leukemia was evaluated by comparing 58 patients who received oral amphotericin B (control group) to 99 patients who received oral posaconazole (posaconazole group). The primary endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
35
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
6
35
3
2
Order By: Relevance
“…The incidence of documented IFIs (definite or probable, according to revised European Organization for Research and Treatment of Cancer [EORTC] criteria) has been reported to range from 12 to 34% in patients with AML (4)(5)(6)(7)(8)(9)(10). In contrast, lower rates of 2 to 6% have been reported for selected patients with AML/myelodysplastic syndrome (MDS) who were enrolled in clinical trials of antifungal prophylaxis (11)(12)(13).…”
mentioning
confidence: 91%
“…The incidence of documented IFIs (definite or probable, according to revised European Organization for Research and Treatment of Cancer [EORTC] criteria) has been reported to range from 12 to 34% in patients with AML (4)(5)(6)(7)(8)(9)(10). In contrast, lower rates of 2 to 6% have been reported for selected patients with AML/myelodysplastic syndrome (MDS) who were enrolled in clinical trials of antifungal prophylaxis (11)(12)(13).…”
mentioning
confidence: 91%
“…Because of the increasing prevalence and changing microbiological spectrum of invasive fungal infections, some form of amphotericin B still provides dependable and broad spectrum therapeutic alternative (Hamill, 2013). Invasive fungal diseases cause morbidity and mortality in patients with AML (Girmenia et al, 2012). Amphotericin B associates with reducing of neutropenic fever in the majority of patients (Spitzer et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, factors such as epidemiologic features of the center, duration of neutropenia or response to the treatment for AML can influence the incidence of IFDs along with the type of the antifungal prophylaxis. Recently, a prospective observational study reported no difference in the incidence of IFDs in AML patients receiving remission-induction or consolidation therapy regarding to the type of AFP contrast to numerous studies in this field [6][7][8][9][10]. Also, a study from Turkey which included 50 patients with AML did not find any difference between posaconazole and fluconazole in terms of AFP failure [11].…”
Section: Introductionmentioning
confidence: 66%